Penguatan Kapasitas SDM dalam Pengelolaan Wisata Berbasis Edukasi - Nugroho, Dhimas Setyo; Suyatno; Hermawan, Hary; Naim, Haniifan Muhammad (Jurnal Abdimas Pariwisata, 2024)
Strengthening Human Resource Capacity in Education-based Tourism Management This Community Service Activity aims to increase community capacity in managing education-based tourism. This PKM activity includes the socialization of Sapta Pesona and cooperation in raising Etawah Peranakan (PE) goats. Through the socialization of SAPTA PESONA, the tourism community in Jogotirto village and El Farm farm gained insight and knowledge about the application of SAPTA PESONA so that they became aware of tourism. Apart from that, the socialization of SAPTA PESONA will enrich the understanding of existing tourist attractions and potential tourism. Through the socialization of cooperation in raising PE goats, the community and tourism actors in Jogotirto village gained an understanding of how to manage PE goats, starting from rearing goats, breeding goats to how to buy and sell goats as well as forming a goat farming cooperation by applying the franchise principle or profit sharing system.